FINANCIAL FAIR PLAY IN EUROPEAN FOOTBALL CLUBS - Abd Ali, Zinah Najem (Transpublika Publisher, 2023)
This research conducts an in-depth analysis of the Fair Play Law as it applies to European Clubs, tracing its origins to its proposal in 2007 and subsequent enactment in 2010. The overarching objective of this legislation is to establish a level and equitable playing field, ensuring that all participating clubs have equal opportunities while concurrently preserving the overall competency and integrity of the sport within the European context. The paper embarks on a comprehensive exploration of the multifaceted concept of fair play within the European football landscape. It seeks to provide a clear and nuanced definition of fair play and to illuminate the intricate web of challenges associated with this concept, with a particular focus on the complexities surrounding club investments and the financial constraints they encounter. Furthermore, the study ventures into the domain of financial and economic dynamics, undertaking a meticulous analysis of the significant challenges precipitated by the Fair Play Law's imposition and subsequent implementation. In doing so, it offers invaluable insights into the profound impact of these regulations on the financial models, budgets, and competitive equilibrium of European football clubs. In essence, this research elucidates the intricate interplay between regulatory measures and the complex economic facets of European club football, underscoring the pursuit of fairness and its profound ramifications on the broader footballing landscape.